Characteristics Of Moromi Sweet Sauce And The Study Of Its Activity On Protein, Sugar And Viscosity Levels - Ida Ningrumsari (Sean Institute, 2024)
The aim of this research was to determine the effect of moromi fermentation on soluble protein content, sugar content and viscosity, with varying salt treatments for 28 days. as well as organoleptic tests. The research design used a completely randomized design (CRD) consisting of 4 treatments and 6 replications. The treatment included fermenting black soybeans by A sojae (Koji) then soaking them in 1000 ml of water with the addition of 0%, 10%, 20% and 30% salt for 28 days (moromi). The parameters analyzed are protein content, sugar content and viscosity and organoleptic tests include color, aroma and taste. The research results showed that the highest protein content was found in the K1 treatment at 1.522%, the sugar content in K1 was 41.227% and the viscosity in K3 was 33.603%. Meanwhile, in terms of organoleptic color, aroma and taste, the panelists liked the product.